Chitin, Characteristic, Sources, and Biomedical Application - Shahbaz, Umar (Current Pharmaceutical Biotechnology, 2020)
Background: Chitin stands at second, after cellulose, as the most abundant polysaccharide in the world. Chitin is found naturally in marine environments as it is a crucial structural component of various marine organisms. Methods: Different amounts of waste chitin and chitosan can be discovered in the environment. Chitinase producing microbes help to hydrolyze chitin waste to play an essential function for the removal of chitin pollution in the Marine Atmosphere. Chitin can be converted by using chemical and biological methods into prominent derivate chitosan. Numerous bacteria naturally have chitin degrading ability. Results: Chitin shows promise in terms of biocompatibility, low toxicity, complete biodegradability, nontoxicity, and film-forming capability. The application of these polymers in the different sectors of biomedical, food, agriculture, cosmetics, pharmaceuticals could be lucrative. Moreover, the most recent achievement in nanotechnology is based on chitin and chitosan-based materials. Conclusion: In this review, we examine chitin in terms of its natural sources and different extraction methods, chitinase producing microbes and chitin, chitosan together with its derivatives for use in biomedical and agricultural applications.
Keywords: chito-oligosaccharides